Natural human interferon-alpha enhances the expression of intracellular adhesion molecule-1, integrin alpha 2 and beta 1 by a mucosal epithelial cell line - Dao, T; Takeuchi, M; Fukuda, S; Kurimoto, M (Folia biologica, 1995)
We have found that pretreatment of a human oral mucosal epithelial cell line KB with natural human interferon-alpha (IFN-alpha) augments the expression of intercellular adhesion molecule-1 (ICAM-1), and the complex of CD29 and CD49b, which is known as very late antigen (VLA)-2, in a dose-dependent manner, whereas the expression of other adhesion molecules such as CD44 leukocyte function associated antigen-3 (LFA-3), VLA-4 and endothelial leukocyte adhesion molecule-1 (ELAM-1) did not show any significant changes under the same conditions. The pretreatment of KB cells with IFN-alpha also induces the adhesion of these cells to the human leukemia T cell line MOLT-16 and to peripheral T lymphocytes in a dose-dependent manner. However, the adhesion of the above-mentioned T cells to KB cells was not inhibited by specific antibodies against ICAM-1, CD29, and CD49b. The results thus show that adhesion molecules other than ICAM-1, CD29, AND CD49b are responsible for the induced adhesion between T cells and IFN-alpha-pretreated KB cells.
Keywords: T-Lymphocytes; Intercellular Adhesion Molecule-1; CD antigeny; Antigens, CD; Epithelium; epitel; Integrin alpha2; buněčné linie; Cell Adhesion; Epithelial Cells; T-lymfocyty; interferon alfa; Cell Line; lidé; integrin alfa2; buněčná adheze; Humans; mezibuněčná adhezivní molekula-1; Integrin beta1; antigeny CD29; Interferon-alpha; epitelové buňky; ústní sliznice; Mouth Mucosa